Exploring plant‐microbe interactions of the rhizobacteria Bacillus subtilis and Bacillus mycoides by use of the CRISPR‐Cas9 system. (26th August 2018) - Yi, Yanglei; Li, Zhibo; Song, Chunxu; Kuipers, Oscar P.
Summary: Bacillus subtilis HS3 and Bacillus mycoides EC18 are two rhizosphere‐associated bacteria with plant growth‐promoting activity. The CRISPR‐Cas9 system was implemented to study various aspects of plant‐microbe interaction mechanisms of these two environmental isolates. The results show that fengycin and surfactin are involved in the antifungal activity of B. subtilis HS3. Moreover, this strain emits several other volatile organic compounds than 2, 3‐butanediol, contributing to plant growth promotion. Confocal laser scanning microscopy observations of the GFP‐labelled strain showed that HS3 selectively colonizes root hairs of grass ( Lolium perenne ) in a hydroponic system. For B. mycoides EC18, we found that the wild‐type EC18 strain and a Δ asbA (petropectin‐deficient) mutant, but not the Δ dhbB (bacillibactin‐deficient) and ADKO ( asbA and dhbB double knockout) mutants, can increase the plant biomass and total chlorophyll. All the mutant strains have a reduced colonization capability on Chinese cabbage ( Brassica rapa ) roots, at the root tip and root hair region compared with the wild‐type strain. These results indicate that the siderophore, bacillibactin, is involved in the plant growth promoting activity and could affect the root colonization of B. mycoides . Collectively, the CRISPR‐Cas9 system we developed for environmental isolates is broadly applicable and will facilitate deciphering the mechanisms of Bacillus ‐plant interactions. © 2018 The Authors.